2012
DOI: 10.3201/eid1803.111358
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Practices and Incidence of Non-O157 Shiga toxin–producingEscherichia coliInfections

Abstract: We surveyed laboratories in Washington State, USA, and found that increased use of Shiga toxin assays correlated with increased reported incidence of non-O157 Shiga toxin–producing Escherichia coli (STEC) infections during 2005–2010. Despite increased assay use, only half of processed stool specimens underwent Shiga toxin testing during 2010, suggesting substantial underdetection of non-O157 STEC infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 4 publications
2
34
0
Order By: Relevance
“…This categorization is based mainly on historic factors: O157 was the first STEC serotype discovered, is the easiest to identify in a microbiology laboratory, and was thought to be more prevalent and virulent than other serotypes. However, studies from around the world have demonstrated that non-O157 serotypes are at least as prevalent as O157 (16)(17)(18). In the United States, epidemiological studies have shown that E. coli O26, O103, and O111 are the non-O157 serotypes most frequently encountered (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This categorization is based mainly on historic factors: O157 was the first STEC serotype discovered, is the easiest to identify in a microbiology laboratory, and was thought to be more prevalent and virulent than other serotypes. However, studies from around the world have demonstrated that non-O157 serotypes are at least as prevalent as O157 (16)(17)(18). In the United States, epidemiological studies have shown that E. coli O26, O103, and O111 are the non-O157 serotypes most frequently encountered (19).…”
mentioning
confidence: 99%
“…Finally, the recent European O104:H4 outbreak was caused by a typical enteroaggregative E. coli strain that has acquired the bacteriophage encoding Stx. This demonstrates that STEC virulence factors encoded on mobile elements could spread among other pathotypes of diarrheagenic E. coli and thereafter represent a public health threat (21,22 (17). Laboratories that test for non-O157 strains use EIAs (17,23).…”
mentioning
confidence: 99%
“…VTEC can be isolated from the faeces of many animals, including ruminants (cattle, sheep and buffalo) and non-ruminant animals (horses, dogs and pigs) (Rivas et al, 2006). The O157 is the most frequently isolated VTEC serogroup, however, several studies showed that non-O157 serogroups have been increasingly isolated (Nielsen et al, 2006;Stigi et al, 2012;Vally et al, 2012), particularly VTEC serogroups O26, O45, O103, O111, O121, and O145 have been referred to as the non O157 VTEC "top six" pathogenic serogroups (Brooks et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While more than 100 STEC serotypes can cause illness in humans (1), traditional testing methods focus primarily on the most common serotype, O157:H7, owing to the ease of its detection using culture-based media. These methods underdetect non-O157 serogroups, and as such, their clinical burden is not well understood (2)(3)(4). Moreover, recent evidence suggests that infections attributed to non-O157 STEC may be more prevalent than those attributed to O157 (1,5), with common serogroups being O26, O45, O103, O111, O121, and O145 in the United States (6,7) and in other countries (1).…”
mentioning
confidence: 99%
“…Given the low prevalence of STEC infections (1 to 2%) (11-13), the associated costs for clinical laboratories for personnel, equipment, and reagents are major barriers for implementation of the recommended universal screening of stool for STEC (4,14). To reduce testing costs, we evaluated the feasibility of a pooled nucleic acid amplification test (NAAT) as an approach for low-cost high-throughput screening for stx 1 and stx 2 from stool.…”
mentioning
confidence: 99%